The Relationship between Homelessness and Behavior Problems among Youth in North Texas: a Brief Report - Reingle Gonzalez, Jennifer M. (American journal of criminal justice, 2018)
This study sought to examine the relationship between homelessness and behavior problems among a community-based sample of youth in North Texas. Data were obtained from a cross-sectional, probability sample of households and a targeted sample of homeless families in Dallas, Texas, with children older than 5 years old ( N = 5232). Parents were asked to report five behavior problems on behalf of their children including arrest or trouble with police, academic problems, behavior problems at school, suspension, and suicide attempts. Logistic and negative binomial regression procedures were used to examine the relationship between homelessness and behavior problems. Youth exposed to homelessness were 36% (OR = 1.63; 95% CI 1.00–1.85) more likely to exhibit any kind of behavior problems than youth who had never experienced homelessness. Homeless youth had 5.51 times the odds of arrest (95% CI 2.60–11.68), 1.74 times the odds of academic problems (95% CI 1.24–2.43), and more than 3 times the odds of suicide attempts (95% CI 1.46, 7.61) than youth who had never been homeless. Homelessness was associated with higher rates of problem behavior, including arrests, academic problems, and suicide attempts. Because homeless youth are commonly enrolled in school and present at health care clinics and emergency departments, clinics and schools may aid in the identification of homeless youth, as well as referral to care. In this way, clinicians may help reduce the burden of behavioral problems that disproportionately affect homeless youth.